HETEROSIS STUDIES FOR FIBRE QUALITY TRAITS IN DIALLEL CROSSES OF UPLAND COTTON (GOSSYPIUM HIRSUTUM L.) - K. S. USHARANI; P. VINDHIYAVARMAN; P. AMALA BALU; N. M. BOOPATHI (The Bioscan, 2015)
Diallel analysis was studied by involving nine parents and their seventy two cross combinations in upland cotton to investigate the best heterotic crosses for fibre quality traits. The hybrid Anjali x KC 2 recorded both highest positive significant relative heterosis (17.18%) and heterobeltiosis (11.81%) and hybrid MCU 5 x Surabhi exhibited highest positive significant standard heterosis (16.98%) for bundle strength. 2.5% span length in parents and their hybrids ranged from 24.03 to 33.51 mm and 27.31 to 36.90 mm, respectively. Thirty four hybrids showed significant negative heterotic effects for micronaire value and hybrid MCU 5 x KC 3 (-27.89%) displayed greater negative standard heterosis. Mean performance of elongation per cent in parents and hybrids was 5.11% and 4.87%, respectively. Out of seventy two hybrids, six cross combinations viz., KC 2 x MCU 5, MCU 5 x MCU 7, Anjali x Suraj, Anjali x MCU 5, Surabhi x Anjali and KC 2 x Suraj were appeared to more promising for most of the fibre quality traits and could be exploited. The present study reveals good scope for isolation of pure lines from the progenies of heterotic F1’s as well as commercial exploitation of heterosis in upland cotton.